Identification of rare and novel deletions that cause (δβ)0‐thalassaemia and hereditary persistence of foetal haemoglobin in Indian population. (15th March 2014) - Mayuranathan, Thiyagaraj; Rayabaram, Janakiram; Das, Reena; Arora, Neeraj; Edison, Eunice S.; Chandy, Mammen; Srivastava, Alok; Velayudhan, Shaji R.
Abstract Objectives Hereditary persistence of foetal haemoglobin (HPFH) and (δβ)0‐thalassaemia are conditions caused by large deletions that involve δ‐ and β‐globin genes in the β‐globin cluster, and they are characterized by increased haemoglobin (HbF) levels in adults. Significant phenotypic diversity is observed between the different mutations that cause these conditions. Molecular characterization of these deletions is important for accurate molecular diagnosis, and they will also provide the information on the cis‐acting genetic regulatory elements present in the β‐globin cluster. Methods We performed gap‐PCR, multiplex ligation‐dependent probe amplification (MLPA), quantitative fluorescent multiplex PCR (QF‐MPCR) and DNA sequencing to detect and characterize the deletions in the β‐globin cluster. Results We characterized six different deletions resulting in (δβ)0‐thalassaemia or HPFH in 51 unrelated families. Conclusion With the help of multiple genetic tools, we performed comprehensive genetic analysis of HPFH and (δβ)0‐thalassaemia in Indian population and could define the molecular basis of these conditions in this population. We also identified two novel HPFH mutations, 49.98 kb (HPFH‐9) and 86.7 kb (HPFH‐10) deletions, in this population.